Analysis of the Unsafe Road User Behavior in Ternate City Using AHP Method - Izzah, Nurul; Sabaruddin, Sabaruddin; Hakim, Raudha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Unsafe road user behavior is something that can affect the implementation of transportation as data from the police states that 61% of accidents are caused by human factors. This study aims to determine the types and factors that cause violations committed by road users who have passed intersection three (Jalan Hasan Esa-Jalan Ahmad Yani) and (Jalan Pemuda-Jalan A.M Kamaruddin) along with the handling of these violations. The results of the analysis found that the most common type of violation was not using a rear helmet by 88.8% caused by not having a helmet. Meanwhile, based on the analysis with the AHP method, the violation that must be prioritized in handling is against the flow with priority alternative handling, including education, sanctions and training.